A lead-free titanate textured ceramic material with low sintering temperature and high piezoelectric performance, and its preparation method and application

By adopting chemicals in BT-based ceramic materials (BA1-XCAX) (TI1-YBY) O3-ZWT.%M-lead-free titanate weaving ceramic material, a low-melting point bracket auxiliary was used to form a liquid phase. The improvement of piezoelectric performance has caused the problem of decreased temperature and high sintering temperature, and realized both high -voltage electricity performance and low -weaving temperature.

CN116903363BActive Publication Date: 2025-01-28HARBIN INST OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310918819.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2025-01-28
Estimated Expiration
2043-07-25

AI Technical Summary

Technical Problem

While improving piezoelectric properties, existing BT-based ceramic materials usually cause a sharp drop in Curie temperature Tc, and high-voltage electrical properties textured ceramics have the problem of high sintering temperature, which limits their application range.

Method used

Using chemical generals (BA1-XCAX) (Ti1-Yby) O3-ZWT.%Mm-free titanate weaving ceramic material, prepared under the conditions of the sintering temperature of 1100 ° C to 1425 ° C, and used the low melting point to use the low melting point The weaving additive M forms a liquid phase, promoting the substrate of the substrate to the template seed crystal or the bracket grain of the substrate, and achieves both high -voltage electrical properties and low -weaving temperatures.

Benefits of technology

Under the premise of maintaining the constant temperature of Curie, the high -voltage electrical performance and the low -weave temperature have been achieved. The factor D33 × G33 is 22.0 × 10-12m2/n.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116903363B_ABST
    Figure CN116903363B_ABST
Patent Text Reader

Abstract

A lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance and a preparation method and application thereof, relating to a lead-free titanate textured ceramic material and a preparation method and application thereof. The problem of enhancing the piezoelectric performance of BT-based ceramic materials under the prior art is that the piezoelectric performance of the ceramic materials is increased at the Curie temperature T c The material chemical formula is (Ba 1‑x Ca x )(Ti 1‑ y B y )O3‑zwt.%M, the elements in the grains are evenly distributed and there is no core-shell structure, the preferred orientation degree is above 96%, the piezoelectric coefficient is above 800pC / N, the field-induced strain coefficient is above 2000pm / V, and the electromechanical conversion factor is 22.0×10 ‑12 m 2 / N or more, and Curie temperature is above 80℃. Methods: 1. Preparation of matrix powder; 2. Preparation of tape casting slurry; 3. Preparation of textured ceramics. Applied in high-performance multilayer environmentally friendly piezoelectric components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lead-free titanate textured ceramic material and a preparation method and application thereof. Background Art

[0002] As an important type of electronic functional material, environmentally friendly BaTiO3 (BT)-based ferroelectric ceramics are expected to be used in the preparation of various electromechanical conversion components, such as piezoelectric actuators, smart sensors, energy harvesters, ultrasonic transducers, etc., due to their relatively outstanding piezoelectric properties, high tunability, and easy preparation. The piezoelectric properties of pure BaTiO3 ceramics are very low, and the piezoelectric coefficient d 33 It is only about 190pC / N. In recent years, in order to improve the piezoelectric properties of BT-based ceramics, researchers have constructed multiphase critical points by designing multi-component solid solutions, ion substitution, doping modification, etc., and combined with traditional ceramic preparation processes to synthesize ceramics with random grain orientation, which has led to a breakthrough improvement in its room temperature piezoelectric properties. However, the enhancement of its piezoelectric properties is usually at the Curie temperature T c The sharp decline in the case of T c The value even drops to 30℃ to 50℃, seriously limiting the use temperature range of this type of material.

[0003] By texturing the grains of piezoelectric ceramics along a specific crystal orientation, the anisotropy of piezoelectric properties and the advantages of engineering domain configuration in improving piezoelectric performance can be effectively utilized, which is expected to significantly improve the piezoelectric performance without sacrificing T c However, to achieve high-quality texture of BaTiO3-based ceramics and thus obtain significantly improved piezoelectric properties, a sintering temperature of more than 1500°C is usually required, which makes it impossible to co-fire textured ceramics with lower-cost metal electrodes, limiting their application in miniaturized and integrated multilayer electronic devices. For example, the preparation of BaTiO3-based ceramics using template seed crystal directional growth technology

[001] c Orientation degree F 001 Up to 98.6% (Ba 0.94 Ca 0.06 )(Ti 0.95 Zr 0.05 )O3 textured ceramics, its d 33 It can reach 750pC / N, which is 2.2 times the level before texturing. However, the ceramic needs to be sintered at 1575℃ to achieve high electrical properties. In addition, since the textured ceramic grains present a "core-shell" composite structure, the deviation of the composite from the initial composition leads to a significant decrease in the Curie temperature of the ceramic. Recently, the literature has reported (Ba 0.972 Ca 0.028 )(Ti 0.86 Sn 0.005 Hf 0.035)O3 ceramics can be textured at lower temperatures, but the

[001] c Orientation degree F 001 Only 84%, its piezoelectric performance is low, d 33 Only ~324pC / N, field-induced strain coefficient S max / E max Only ~575pm / V. In summary, how to reduce T c It is still a challenging problem in the research field to achieve a significant improvement in the piezoelectric properties of BaTiO3-based ferroelectric ceramics and a significant reduction in the texture temperature under the premise of... Summary of the invention

[0004] The present invention aims to solve the problem that the piezoelectric properties of BT-based ceramic materials are usually enhanced at the Curie temperature T c This is achieved under the condition of a sharp drop, and the high-voltage electrical performance textured ceramic has the problem of high sintering temperature, and provides a lead-free titanate textured ceramic material that takes into account both low sintering temperature and high-voltage electrical performance, as well as a preparation method and application thereof.

[0005] A lead-free titanate textured ceramic material that combines low sintering temperature with high piezoelectric properties. Its chemical formula is (Ba 1-x Ca x )(Ti 1-y B y )O3-zwt.%M, wherein B is one of Zr, Sn and Hf or a combination of several thereof, M is Li2CO3, CuO, Bi2O3, or a mixture of CuO and Li2CO3, or a mixture of Bi2O3 and Li2CO3, and 0 <x<0.15,0<y<0.10,0<z<3;

[0006] The lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance is obtained under the condition of sintering temperature of 1100°C to 1425°C, and the lead-free titanate textured ceramic material is prepared along

[001] c ,

[110] c or

[111] c The preferred orientation of the grain composition, the elements in the grain are evenly distributed and there is no core-shell structure, the preferred orientation degree is more than 96%, and the piezoelectric coefficient d 33 More than 800pC / N, field-induced strain coefficient S max / E max More than 2000pm / V, electromechanical conversion factor d 33 ×g 33 22.0×10 -12 m 2 / N or above, and the Curie temperature is above 80℃.

[0007] A preparation method of a lead-free titanate textured ceramic material that takes into account low sintering temperature and high piezoelectric properties, which is completed according to the following steps:

[0008] I. Preparation of matrix fine powder:

[0009] ① Based on the chemical stoichiometric ratio of the textured ceramic target composition with the general chemical formula (Ba 1-x Ca x )(Ti 1-y B y )O3 - zwt.%M, weigh BaCO3 powder, CaCO3 powder, TiO2 powder, B oxide and template seed crystal. Among them, the B oxide is one or a combination of ZrO2, SnO2 and HfO2, and 0 < x < 0.15, 0 < y < 0.10, 0 < z < 3; the particle sizes of the TiO2 powder and the B oxide are both below 100 nm;

[0010] ② Ball-mill and dry the weighed BaCO3 powder, CaCO3 powder, TiO2 powder and B oxide to obtain a mixed raw material;

[0011] ③ Pre-sinter the mixed raw material at a temperature of 950 °C to 1350 °C for 1 h to 4 h to obtain pure perovskite phase fine powder; the pure perovskite phase fine powder is a pure phase and the particle size is less than 300 nm;

[0012] ④ Based on the chemical stoichiometric ratio of the textured ceramic target composition with the general chemical formula (Ba 1-x Ca x )(Ti 1-y B y )O3 - zwt.%M, weigh M, then mix M with the pure perovskite phase fine powder and perform secondary ball-milling to obtain M-doped matrix fine powder; where M is Li2CO3, CuO, Bi2O3, or a mixture of CuO and Li2CO3, or a mixture of Bi2O3 and Li2CO3, and 0 < x < 0.15, 0 < y < 0.10, 0 < z < 3;

[0013] II. Preparation of tape-casting slurry:

[0014] Using BaTiO3 flake seed crystal or CaTiO3 flake seed crystal as the template seed crystal and the M-doped matrix fine powder as the matrix fine powder, ball-mill and mix the matrix fine powder, solvent, dispersant, binder and plasticizer for 24 h to 48 h, then add the template seed crystal and continue ball-milling for 15 min to 45 min, and finally perform vacuum degassing to obtain a tape-casting slurry with uniform dispersion and good fluidity;

[0015] Both the BaTiO3 flake seed crystal and the CaTiO3 flake seed crystal are along

[001] c ,

[110] cor

[111] c Preferred orientation and diameter-thickness ratio ≥ 8; the molar ratio of the template seed crystal to the matrix fine powder is a: (100-a), wherein 0 <a<20;

[0016] 3. Preparation of textured ceramics:

[0017] ① At a casting speed of 0.5 cm / s to 10 cm / s, a casting machine is used to cast and dry the casting slurry with uniform dispersion and good fluidity to obtain a membrane sheet;

[0018] ② Cut and stack the membrane, and then perform hot pressing, hot water uniform pressing, binder removal and cold isostatic pressing in sequence to obtain a ceramic green body;

[0019] ③ Sintering the ceramic green body at a temperature of 1100°C to 1425°C for 15 minutes to 20 hours to obtain a lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric properties.

[0020] The invention discloses an application of a lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance, which is applied to high-performance multilayer structured environmentally friendly piezoelectric components.

[0021] Principle: This invention adopts a new design strategy different from the previous BT-based ceramic research, selecting pure perovskite phase and multi-phase coexistence at room temperature (Ba 1-x Ca x )(Ti 1-y B y)O3 - zwt.%M, where B is one or a combination of Zr, Sn, and Hf, M is Li2CO3, CuO, Bi2O3, or a mixture of CuO and Li2CO3, or a mixture of Bi2O3 and Li2CO3, and 0 < x < 0.15, 0 < y < 0.10, 0 < z < 3. In the present invention, by adding a low - melting - point texture - promoting agent M, a liquid phase is formed in the ceramic at a low temperature during the sintering process and exists in the form of a metastable liquid film on the surface of the template seed crystals or textured grains. The existence of the liquid - film layer is conducive to the dissolution of randomly - oriented matrix fine grains therein, and then the precipitation on the oriented grains, thereby greatly promoting the mass transfer behavior of the matrix to the template seed crystals or textured grains, significantly improving the orientation quality while reducing the sintering temperature. In addition, the ceramic components designed in the present invention co - exist in multiple phases and are textured ceramics along a specific orientation. It can not only utilize the advantage of maximizing the piezoelectric performance in the preferred orientation, but also utilize the advantages of the multi - domain configuration of 4R and 4O engineering domains and the promotion of polarization reversal by the miniaturization of electric domains, and can also utilize the stretching effect of the 1T configuration on polarization. Moreover, the reduction of the potential barrier between the phases also promotes the polarization rotation and stretching. Furthermore, the template seed crystals of the prepared textured ceramics are completely dissolved in the oriented grains, the core - shell structure in the textured grains disappears, all elements are uniformly distributed, and there is no influence of lattice mismatch and mechanical clamping in the core - shell structure on the temperature - induced phase - change behavior. The above mechanisms work together, enabling the present invention to achieve both high piezoelectric performance and low texture temperature on the premise of maintaining the phase - change temperature T c Under the premise of c , the present invention achieves both high piezoelectric performance and low texture temperature.

[0022] Advantages of the present invention: It solves the problem that the enhancement of the piezoelectric performance of BT - based ceramic materials in the prior art is usually achieved under the condition that the Curie temperature T c significantly decreases, and there is a problem of high sintering temperature for textured ceramics with high piezoelectric performance. The (Ba 1-x Ca x )(Ti 1-y B y )O3 - zwt.%M textured ceramics have a preferred orientation degree of more than 96% along

[001] c ,

[110] c or

[111] c . The elements in the grains are uniformly distributed and there is no core - shell structure. The piezoelectric coefficient d 33 is above 800 pC / N, the field - induced strain coefficient S max / E max is above 2000 pm / V, and the electromechanical conversion factor d 33 ×g 33 is 22.0×10 -12 m 2 N -1The above, Curie temperature is above 80°C, and these electrical properties can be obtained when the sintering temperature of the textured ceramic is not higher than 1425°C. In other words, the present invention achieves both high voltage electrical performance and low texture temperature under the premise of keeping the Curie temperature unchanged. The present invention can provide a design and preparation idea for the future development of new materials with high performance and low firing characteristics, and can also expand the scope of use of BT-based textured ceramic materials into high-performance piezoelectric components with multilayer structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The XRD spectrum of the lead-free titanate textured ceramic material prepared in Example 1 with both low sintering temperature and high piezoelectric performance;

[0024] Figure 2 To compare the relationship between the texture degree of the lead-free titanate textured ceramic material with low sintering temperature and high piezoelectric performance prepared in Experiment 2 and Example 1;

[0025] Figure 3 The dielectric temperature spectrum of the lead-free titanate textured ceramic material prepared in Example 1 with both low sintering temperature and high piezoelectric performance;

[0026] Figure 4 The field-induced strain curve changes of the ceramics of Example 1 and Comparative Experiment 1 before and after adding the texture aid and texturing;

[0027] Figure 5 The piezoelectric coefficient and electromechanical conversion coefficient of the ceramics of Example 1 and Comparative Experiment 1 before and after adding the texturing aid and texturing;

[0028] Figure 6 This is a microscopic morphology of the lead-free titanate textured ceramic material prepared in Example 2 with both low sintering temperature and high piezoelectric performance;

[0029] Figure 7 This is the XRD pattern of the lead-free titanate textured ceramic material prepared in Example 3, which has both low sintering temperature and high piezoelectric properties. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0031] Specific implementation method 1: This implementation method is a lead-free titanate textured ceramic material that takes into account both low sintering temperature and high piezoelectric performance. Its chemical formula is (Ba 1-x Ca x )(Ti 1-y B y)O3-zwt.%M, wherein B is one of Zr, Sn and Hf or a combination of several thereof, M is Li2CO3, CuO, Bi2O3, or a mixture of CuO and Li2CO3, or a mixture of Bi2O3 and Li2CO3, and 0 <x<0.15,0<y<0.10,0<z<3;

[0032] The lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance is obtained under the condition of sintering temperature of 1100°C to 1425°C, and the lead-free titanate textured ceramic material is prepared along

[001] c ,

[110] c or

[111] c The preferred orientation of the grain composition, the elements in the grain are evenly distributed and there is no core-shell structure, the preferred orientation degree is more than 96%, and the piezoelectric coefficient d 33 More than 800pC / N, field-induced strain coefficient S max / E max More than 2000pm / V, electromechanical conversion factor d 33 ×g 33 22.0×10 -12 m 2 / N or above, and the Curie temperature is above 80℃.

[0033] Beneficial effects of this specific implementation method:

[0034] The problem that the piezoelectric properties of BT-based ceramic materials are usually enhanced at the Curie temperature T c The sintering temperature of the high-voltage electrical performance textured ceramic is high. 1-x Ca x )(Ti 1-y B y )O3-zwt.%M textured ceramic grains along

[001] c ,

[110] c or

[111] c The preferred orientation degree is above 96%, the elements in the grains are evenly distributed and there is no core-shell structure. The piezoelectric coefficient d 33 More than 800pC / N, field-induced strain coefficient S max / E max More than 2000pm / V, electromechanical conversion factor d 33 ×g 33 22.0×10 -12 m 2 N -1As described above, the Curie temperature is 80 °C or higher, and these electrical properties can be obtained when the sintering temperature of the textured ceramic is not higher than 1425 °C. In other words, under the premise of keeping the Curie temperature unchanged, this specific embodiment achieves a balance between high piezoelectric properties and low texturing temperature. This specific embodiment can provide a design and preparation idea for the future research and development of new materials with high performance and low sintering characteristics, and can also expand the application range of BT-based textured ceramic materials into high-performance piezoelectric components with multilayer structures.

[0035] Specific Embodiment 2: A preparation method of a lead-free titanate textured ceramic material that takes into account low sintering temperature and high piezoelectric properties, which is completed according to the following steps:

[0036] I. Preparation of matrix fine powder:

[0037] ① Weigh BaCO3 powder, CaCO3 powder, TiO2 powder, B oxide and template seed crystal according to the stoichiometric ratio of the chemical general formula of the target composition of the textured ceramic (Ba 1-x Ca x )(Ti 1-y B y )O3 - zwt.%M. Among them, the B oxide is one or a combination of ZrO2, SnO2 and HfO2, and 0 < x < 0.15, 0 < y < 0.10, 0 < z < 3; the particle sizes of the TiO2 powder and the B oxide are both below 100 nm;

[0038] ② Ball-mill and dry the weighed BaCO3 powder, CaCO3 powder, TiO2 powder and B oxide to obtain a mixed raw material;

[0039] ③ Pre-sinter the mixed raw material at a temperature of 950 °C to 1350 °C for 1 h to 4 h to obtain pure perovskite-phase fine powder; the pure perovskite-phase fine powder is a pure phase and its particle size is less than 300 nm;

[0040] ④ Weigh M according to the stoichiometric ratio of the chemical general formula of the target composition of the textured ceramic (Ba 1-x Ca x )(Ti 1-y B y )O3 - zwt.%M, and then mix M with the pure perovskite-phase fine powder and perform secondary ball-milling to obtain matrix fine powder doped with M; where M is Li2CO3, CuO, Bi2O3, or a mixture of CuO and Li2CO3, or a mixture of Bi2O3 and Li2CO3, and 0 < x < 0.15, 0 < y < 0.10, 0 < z < 3;

[0041] II. Preparation of tape-casting slurry:

[0042] BaTiO3 flake seed crystals or CaTiO3 flake seed crystals are used as template seed crystals, M-doped matrix fine powder is used as matrix fine powder, the matrix fine powder, solvent, dispersant, binder and plasticizer are ball-milled for 24h to 48h, then the template seed crystals are added and ball-milled for 15min to 45min, and finally vacuum bubbling is performed to obtain a casting slurry with uniform dispersion and good fluidity;

[0043] The BaTiO3 flake seed crystals and the CaTiO3 flake seed crystals are all along

[001] c ,

[110] c or

[111] c Preferred orientation and diameter-thickness ratio ≥ 8; the molar ratio of the template seed crystal to the matrix fine powder is a: (100-a), wherein 0 <a<20;

[0044] 3. Preparation of textured ceramics:

[0045] ① At a casting speed of 0.5 cm / s to 10 cm / s, a casting machine is used to cast and dry the casting slurry with uniform dispersion and good fluidity to obtain a membrane sheet;

[0046] ② Cut and stack the membrane, and then perform hot pressing, hot water uniform pressing, binder removal and cold isostatic pressing in sequence to obtain a ceramic green body;

[0047] ③ Sintering the ceramic green body at a temperature of 1100°C to 1425°C for 15 minutes to 20 hours to obtain a lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric properties.

[0048] Specific implementation method 3: This implementation method is different from specific implementation method 2 in that the purity of BaCO3 powder, CaCO3 powder, TiO2 powder and B oxide described in step 1① is ≥99.8%; the purity of M described in step 1④ is ≥99.8%. Other aspects are the same as specific implementation method 2.

[0049] Specific embodiment 4: This embodiment is different from specific embodiment 2 or 3 in that: the ball milling mixing described in step 1② is specifically carried out under the condition of a rotation speed of 240r / min to 480r / min for 24h to 96h; the secondary ball milling time described in step 1④ is 24h to 96h. Others are the same as specific embodiment 2 or 3.

[0050] Specific embodiment 5: This embodiment is different from specific embodiments 2 to 4 in that: the solvent in step 2 is a xylene-ethanol mixed solution; the dispersant in step 2 is melted herring oil; the binder in step 2 is polyvinyl butyral; the plasticizer in step 2 is polyalkylene glycol and butyl benzyl phthalate. The rest is the same as specific embodiments 2 to 4.

[0051] Specific implementation method 6: This implementation method is different from specific implementation methods 2 to 5 in that the vacuum bubbling time in step 2 is 1 hour to 12 hours. The rest is the same as specific implementation methods 2 to 5.

[0052] Specific embodiment 7: This embodiment is different from specific embodiments 2 to 6 in that the thickness of the membrane described in step 3① is 10 μm to 100 μm. The rest is the same as specific embodiments 2 to 6.

[0053] Specific implementation eight: This implementation differs from any one of specific implementations two to seven in that: the hot pressing described in step three ② is specifically hot pressing at a temperature of 50℃~120℃ and 5MPa~75MPa; the hot water uniform pressing described in step three ② is specifically hot water uniform pressing at a temperature of 60℃~95℃ and 20MPa~50MPa; the debinding described in step three ② is specifically heating up to 500℃~675℃ at a heating rate of 0.1℃ / min~0.6℃ / min, and then keeping the temperature at 500℃~675℃ for 1h~6h; the cold isostatic pressing described in step three ② is specifically keeping the pressure at a temperature of 150MPa~300MPa for 1min~6min. The rest is the same as specific implementations two to seven.

[0054] Specific implementation method 9: This implementation method is an application of a lead-free titanate textured ceramic material that takes into account both low sintering temperature and high piezoelectric performance. It is applied to high-performance multi-layer structure environmentally friendly piezoelectric components.

[0055] Specific embodiment 10: This embodiment differs from specific embodiment 9 in that the high-performance multi-layered environmentally friendly piezoelectric component is a multi-layer piezoelectric driver, a multi-layer energy collector, a multi-layer sensor, a multi-layer ultrasonic transducer or a multi-layer piezoelectric sensor. The rest is the same as specific embodiment 9.

[0056] The following examples are used to verify the beneficial effects of the present invention:

[0057] Embodiment 1:

[0058] A method for preparing a lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance is completed by the following steps:

[0059] 1. Preparation of matrix fine powder:

[0060] ① The target chemical formula of textured ceramics is (Ba 0.95 Ca 0.05 )(Ti 0.92 Zr 0.06 Sn 0.02) BaCO3 powder, CaCO3 powder, TiO2 powder, ZrO2, SnO2 and template seed crystals are weighed based on the stoichiometric ratio of MgO3-0.4wt.%Li2CO3; the particle sizes of the TiO2 powder, ZrO2 and SnO2 are all below 100nm;

[0061] ② At a rotation speed of 360 r / min, the weighed BaCO3 powder, CaCO3 powder, TiO2 powder, ZrO2 and SnO2 were ball-milled for 48 hours, and finally dried to obtain a mixed raw material;

[0062] ③ Pre-calcining the mixed raw materials at a temperature of 1150° C. for 2 hours to obtain pure perovskite phase fine powder; the pure perovskite phase fine powder is pure phase and has an average particle size of 270 nm;

[0063] ④ The target chemical formula of the textured ceramic is (Ba 0.95 Ca 0.05 )(Ti 0.92 Zr 0.06 Sn 0.02 )O3-0.4wt.%Li2CO3 stoichiometric ratio is taken as the basis, and then Li2CO3 and pure perovskite phase fine powder are mixed and ball-milled for a second time for 48h to obtain M-doped matrix fine powder;

[0064] 2. Casting slurry preparation:

[0065] BaTiO3 flake seed crystals were used as template seed crystals, M-doped matrix fine powder was used as matrix fine powder, matrix fine powder, solvent, dispersant, binder and plasticizer were ball-milled for 24 hours, then template seed crystals were added and ball-milled for 30 minutes, and finally vacuum-bubbled for 2 hours to obtain a casting slurry with uniform dispersion and good fluidity;

[0066] The BaTiO3 flake seed crystal is along

[001] c Preferred orientation and diameter-to-thickness ratio ≥ 8; the molar ratio of the template seed crystal to the matrix fine powder is 5:95;

[0067] 3. Preparation of textured ceramics:

[0068] ① At a casting speed of 1 cm / s, a casting machine is used to cast and dry the casting slurry with uniform dispersion and good fluidity to obtain a membrane; the membrane has a thickness of 40 μm;

[0069] ② Cut and stack the membrane, and then perform hot pressing, hot water uniform pressing, binder removal and cold isostatic pressing in sequence to obtain a ceramic green body;

[0070] ③ The ceramic green body is sintered at a temperature of 1425°C for 9 hours to obtain a lead-free titanate textured ceramic material with both low sintering temperature and high piezoelectric properties.

[0071] The purity of the BaCO3 powder, CaCO3 powder, TiO2 powder, ZrO2 and SnO2 described in step 1① is ≥99.8%; the purity of the Li2CO3 described in step 1④ is ≥99.8%.

[0072] The solvent in step 2 is a xylene-ethanol mixed solution, and the mass ratio of xylene to ethanol is 1:1;

[0073] The dispersant in step 2 is melted herring oil; the binder in step 2 is polyvinyl butyral; the plasticizer in step 2 is polyalkylene glycol and butyl benzyl phthalate, and the mass ratio of the polyalkylene glycol to butyl benzyl phthalate is 1:1;

[0074] The volume ratio of the base powder to the solvent in step 2 is 23.6:64.0; the volume ratio of the base powder to the dispersant in step 2 is 23.6:2.1; the volume ratio of the base powder to the binder in step 2 is 23.6:5.4; the volume ratio of the base powder to the plasticizer in step 2 is 23.6:4.9;

[0075] The hot pressing described in step 3② is specifically hot pressing for 15 minutes at a temperature of 75°C and 20MPa; the hot water uniform pressing described in step 3② is specifically hot water uniform pressing for 15 minutes at a temperature of 75°C and 20MPa; the debinding described in step 3② is specifically heating up to 600°C at a heating rate of 0.2°C / min, and then keeping warm at 600°C for 2h; the cold isostatic pressing described in step 3② is specifically keeping the pressure at a temperature of 200MPa for 3min.

[0076] The above-mentioned lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance has a general chemical formula of (Ba 0.95 Ca 0.05 )(Ti 0.92 Zr 0.06 Sn 0.02 )O3-0.4wt.%Li2CO3;

[0077] The lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance as described in Example 1 is made of

[001] c The preferred orientation of the grain composition, EDS element distribution results show that the elements in the grain are evenly distributed and there is no core-shell structure, the preferred orientation degree is 98%, and the piezoelectric coefficient d 33 The field-induced strain coefficient S is 820pC / N. max / E max is 2040pm / V, the electromechanical conversion factor is d33 ×g 33 23.5×10 -12 m 2 / N, Curie temperature is 83℃.

[0078] Comparative Experiment 1: The difference between this comparative experiment and Example 1 is that no BaTiO3 flake seed crystals are added, and the ceramic is non-textured. No 0.4wt.% Li2CO3 sintering aid is added, and the final composition of the ceramic is (Ba 0.95 Ca 0.05 )(Ti 0.92 Zr 0.06 Sn 0.02 )O3. Others are the same as those in the first embodiment.

[0079] Comparative Experiment 2: The difference between this comparative experiment and Example 1 is that in step 3③, the ceramic green body is sintered at a temperature of 1200℃, 1250℃, 1300℃, 1325℃, 1350℃ or 1400℃ for 5min; or in step 3③, the ceramic green body is sintered at a temperature of 1400℃, 1500℃, 1550℃ or 1575℃ for 9h. The rest is the same as Example 1.

[0080] Figure 1 This is the XRD spectrum of the lead-free titanate textured ceramic material prepared in Example 1 with both low sintering temperature and high piezoelectric performance; it can be seen from the figure that the ceramic has a pure perovskite phase structure, and according to the powder XRD refinement results, it is a coexistence of rhombohedral R phase, orthorhombic O phase and tetragonal T phase. The (001) and (002) peak intensities of the textured ceramic are very strong, and the non-{001} peak intensity is very weak, indicating that the ceramic has a strong

[001] c Orientation. Using the Lotgering factor (F 00l ) method is used to calculate the ceramic texture degree shown in the XRD pattern, and it can be obtained that along

[001] c The orientation degree F 00l For textured ceramics, F 00l The value range is 0 <F 00l <1, F 00l The larger the value, the higher the degree of <00l> orientation of the ceramic. 00l It is 98%.

[0081] Figure 2To compare the relationship between the texture degree of the lead-free titanate textured ceramic material with low sintering temperature and high voltage electrical performance prepared in Experiment 2 and Example 1, it can be seen from the figure that under the premise of 5 minutes of heat preservation, as the sintering temperature rises from 1200℃ to 1400℃, the texture factor rises sharply and reaches 85% at 1400℃. When the heat preservation time is extended to 9h, the texture factor reaches 96% at 1400℃, and the texture factor continues to rise as the sintering temperature continues to increase, and reaches 98% at 1425℃.

[0082] Figure 3 The dielectric temperature spectrum of the lead-free titanate textured ceramic material prepared in Example 1 with both low sintering temperature and high piezoelectric performance; it can be seen from the figure that the phase transition temperature T R-O and T O-T are all near room temperature, proving that ceramics coexist in multiple phases at room temperature, and the Curie temperature T c At 83°C.

[0083] Figure 4 The field-induced strain curves of the ceramics in Example 1 and Comparative Experiment 1 before and after adding the texture additive and texturing are shown in the figure. It can be seen from the figure that the high-field piezoelectric coefficient S of the ceramics without the texture additive and texture is max / E max The high-field piezoelectric coefficient S is 840 pm / V. max / E max As high as 2040pm / V, it is 2.4 times higher than that before texturing, and this is achieved without lowering the Curie temperature (the Curie temperature in comparative experiment 1 is 80°C), and the sintering temperature for achieving this excellent performance is only 1425°C, showing the advantages of this invention.

[0084] Figure 5 The piezoelectric coefficient and electromechanical conversion coefficient of the ceramics in Example 1 and Comparative Experiment 1 before and after adding the texture additive and texturing are shown in the figure. It can be seen from the figure that the piezoelectric coefficient d of the ceramics without the texture additive and texture is 33 and electromechanical conversion coefficient d 33 ×g 33 353pC / N and 5.5×10 -12 m 2 / N, the high field piezoelectric coefficient d after adding sintering aids and texturing 33 and electromechanical conversion coefficient d 33 ×g 33 820pC / N and 23.5×10 -12 m 2 / N, which is 2.3 and 4.3 times higher than before texturing, and is achieved without lowering the Curie temperature. Moreover, the sintering temperature for achieving this excellent performance is only 1425°C, demonstrating the advantages of this invention.

[0085] Embodiment 2: This embodiment is different from the embodiment 1 in that: a lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance, its chemical formula is (Ba 0.95 Ca 0.05 )(Ti 0.92 Zr 0.06 Sn 0.02 )O3-0.6wt.%M, wherein M is a combination of CuO and Li2CO3 in a molar ratio of 1:2; Step 3① The casting speed is 2cm / s, and the thickness of the membrane is 30μm; Step 3③ The ceramic green body is sintered at a temperature of 1375℃ for 9h. The rest is the same as in Example 1.

[0086] The lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance as described in Example 2 is made of

[001] c The preferred orientation of the grain composition, the elements in the grain are evenly distributed and there is no core-shell structure. The preferred orientation degree is 98%, and the piezoelectric coefficient d 33 The field-induced strain coefficient S is 860pC / N. max / E max is 2110pm / V, the electromechanical conversion factor is d 33 ×g 33 24.9×10 -12 m 2 / N, Curie temperature is 81℃.

[0087] Figure 6 This is a microscopic morphology of the lead-free titanate textured ceramic material prepared in Example 2 that has both low sintering temperature and high piezoelectric properties. As can be seen from the figure, the ceramic textured at 1375°C has clear grain boundaries, dense grain growth, uniform grain size, and high texture quality.

[0088] Embodiment 3: This embodiment is different from the embodiment 1 in that: a lead-free titanate textured ceramic material having both low sintering temperature and high voltage electrical performance is used, and its chemical formula is (Ba 0.98 Ca 0.02 )(Ti 0.96 Sn 0.04)O3-0.4wt.%Li2CO3, the molar ratio of the template seed crystal to the matrix fine powder is 4:96, the hot pressing described in step 3② is specifically hot pressing at a temperature of 80℃ and 40MPa for 10min, the hot water uniform pressing described in step 3② is specifically hot water uniform pressing at a temperature of 85℃ and 45MPa for 10min; step 3③ sintering the ceramic green body at a temperature of 1375℃ for 5h. The rest is the same as in Example 1.

[0089] The lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance as described in the third embodiment is made of

[001] c The preferred orientation of the grain composition, the elements in the grain are evenly distributed and there is no core-shell structure. The preferred orientation degree is 98%, and the piezoelectric coefficient d 33 is 806pC / N, and the field-induced strain coefficient S max / E max is 2004pm / V, the electromechanical conversion factor is d 33 ×g 33 22.3×10 -12 m 2 / N, Curie temperature is 90℃.

[0090] Figure 7 The XRD pattern of the lead-free titanate textured ceramic material prepared in Example 3 with both low sintering temperature and high piezoelectric performance; it can be seen from the figure that the (001) and (002) peak intensities of the textured ceramic are very strong, and the non-{001} peak intensity is very weak, indicating that the ceramic has a strong

[001] c Orientation, its texture factor F 00l It is 98%.

Claims

1. A lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance, characterized in that Its chemical formula is (Ba 1-x Ca x )(Ti 1-y B y )O3-zwt.%M, wherein B is Sn, or a combination of Zr and Sn, M is Li2CO3, Bi2O3, or a mixture of CuO and Li2CO3, or a mixture of Bi2O3 and Li2CO3, and 0 <x<0.15,0<y<0.10,0<z<3; The lead-free titanate textured ceramic material is made from [001] c ,[110] c or[111] c The preferred orientation of the grain composition, the elements in the grain are evenly distributed and there is no core-shell structure. The preferred orientation degree is more than 96%, and the piezoelectric coefficient d 33 The field-induced strain coefficient is above 800pC / N. S max / E max The electromechanical energy conversion factor is above 2000pm / V. d 33 × g 33 22.0×10 -12 m 2 / N or above, Curie temperature is above 80℃; The method for preparing the lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance is completed by the following steps:

1. Preparation of matrix fine powder: ①Based on the stoichiometric ratio of the target composition chemical general formula of the lead-free titanate textured ceramic material as (Ba 1-x Ca x )(Ti 1-y B y )O3 - zwt.%M, weigh BaCO3 powder, CaCO3 powder, TiO2 powder, B oxide and template seed crystal, where the B oxide is SnO2, or a combination of ZrO2 and SnO2, and 0 < x < 0.15, 0 < y < 0.10, 0 < z < 3; the particle sizes of the TiO2 powder and the B oxide are both below 100 nm; ② At a rotation speed of 240 r / min to 480 r / min, ball-mill the weighed BaCO3 powder, CaCO3 powder, TiO2 powder and B oxide for 24 h to 96 h and dry to obtain a mixed raw material; ③ Pre-calcining the mixed raw materials at a temperature of 1150° C. to 1350° C. for 1 h to 4 h to obtain pure perovskite phase fine powder; the pure perovskite phase fine powder is pure phase and has a particle size of less than 300 nm; ④ The target chemical formula of lead-free titanate textured ceramic material is (Ba 1-x Ca x )(Ti 1-y B y )O3-zwt.%M stoichiometric ratio is taken as the basis, M is weighed, and then M is mixed with pure perovskite phase fine powder and subjected to secondary ball milling for 24h~96h to obtain matrix fine powder; wherein M is Li2CO3, Bi2O3, or a mixture of CuO and Li2CO3, or a mixture of Bi2O3 and Li2CO3, and 0 <x<0.15,0<y<0.10,0<z<3; 2. Casting slurry preparation: BaTiO3 flake seed crystals or CaTiO3 flake seed crystals are used as template seed crystals, matrix fine powder, solvent, dispersant, binder and plasticizer are ball-milled for 24h~48h, then the template seed crystals are added and ball-milled for 15min~45min, and finally vacuum-bubbled for 1h~12h to obtain a casting slurry with uniform dispersion and good fluidity; The BaTiO3 flake seed crystals and the CaTiO3 flake seed crystals are all along [001] c ,[110] c or[111] c Preferred orientation and diameter-thickness ratio ≥ 8; the molar ratio of the template seed crystal to the matrix fine powder is a: (100-a), wherein 0 <a<20; The volume ratio of the base powder to the solvent is 23.6:64.0; the volume ratio of the base powder to the dispersant is 23.6:2.1; the volume ratio of the base powder to the binder is 23.6:5.4; the volume ratio of the base powder to the plasticizer is 23.6:4.9; 3. Preparation of textured ceramics: ① Use a casting machine to cast and dry the casting slurry with uniform dispersion and good fluidity to obtain a membrane sheet at a casting speed of 0.5cm / s~10cm / s; ② Cut and stack the membrane, and then perform hot pressing, hot water uniform pressing, binder removal and cold isostatic pressing in sequence to obtain a ceramic green body; The debinding process is specifically to increase the temperature to 500°C to 675°C at a heating rate of 0.1°C / min to 0.6°C / min, and then keep the temperature at 500°C to 675°C for 1h to 6h; ③ Sinter the ceramic green body at a temperature of 1375°C~1425°C for 15min~20h to obtain a lead-free titanate textured ceramic material with both low sintering temperature and high piezoelectric properties.

2. The lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance according to claim 1, characterized in that The purity of the BaCO3 powder, CaCO3 powder, TiO2 powder and B oxide described in step 1① is ≥99.8%; the purity of M described in step 1④ is ≥99.8%.

3. The lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance according to claim 1, characterized in that The solvent described in step 2 is a xylene-ethanol mixed solution; the dispersant described in step 2 is molten herring oil; the adhesive described in step 2 is polyvinyl butyral; and the plasticizer described in step 2 is polyalkylene glycol and butyl benzyl phthalate.

4. The lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance according to claim 1, characterized in that The thickness of the membrane described in step 3① is 10μm~100μm.

5. The lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance according to claim 1, characterized in that The hot pressing described in step 3② is specifically hot pressing at a temperature of 50°C~120°C and 5MPa~75MPa; the hot water uniform pressing described in step 3② is specifically hot water uniform pressing at a temperature of 60°C~95°C and 20MPa~50MPa; the cold isostatic pressing described in step 3② is specifically at a temperature of 150MPa~300MPa, and the pressure is maintained for 1min~6min.

6. The use of a lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance as claimed in claim 1, characterized in that It is used in high-performance multi-layered environmentally friendly piezoelectric components.

7. The use of a lead-free titanate textured ceramic material having both low sintering temperature and high piezoelectric performance according to claim 6, characterized in that The high-performance multi-layered environmentally friendly piezoelectric component is a multi-layer piezoelectric driver, a multi-layer energy collector, a multi-layer sensor or a multi-layer ultrasonic transducer.

Citation Information

Patent Citations

  • Lead-free piezoelectric texture composite material applied in high-power-density energy collection device and preparation method and application thereof

    CN109400147A